The Effect of The Rupiah Exchange Rate on Inflation-Mediated Stock Prices in PT Unilever Indonesia Tbk - Aprillia, Resita; Prasetya, Bangun Putra (Journal Of Management Analytical and Solution (JoMAS), 2024)
Indonesia's large population presents significant opportunities for the consumer goods industry. However, a company's ability to sustain its stock price requires careful consideration of macroeconomic variables. This study investigates the effect of the Rupiah exchange rate on the stock price of PT Unilever Indonesia Tbk during the period from 2022 to 2023. Employing a quantitative approach, the research examines macroeconomic data, particularly the Rupiah exchange rate, obtained from Bank Indonesia. Using purposive sampling, the study focuses on data relevant to the research period. Multiple linear regression analysis is applied to assess the relationship between the Rupiah exchange rate and stock price. The findings reveal that the Rupiah exchange rate has a significant impact on the stock price of PT Unilever Indonesia Tbk.